Streptococcus pneumoniae: sensibilidade a antimicrobianos e detecção de genes de resistência em isolados de crianças com pneumonia adquirida na comunidade em Fortaleza, Ceará. - Oliveira, Nayara Santos de (2013)
Acute respiratory infection (ARI) is a clinical syndrome, in which about 80% of deaths attributed to pneumonia, a serious disease that affects the lower respiratory tract. The common etiologic agent in community-acquired pneumonia (CAP) is Streptococcus pneumoniae (S. pneumoniae). Pneumococcal diseases begin with colonization of S. pneumoniae in the nasopharynx and may progress to invasive disease. In recent decades, the increasing number of strains of S. pneumoniae resistant to β-lactam antibiotics and macrolides has hindered the treatment of pneumococcal infections. The objectives of this study were to determine the prevalence of carriers of S. pneumoniae in children with CAP, the sensitivity profile to antibiotics and serotype distribution in Fortaleza, Brazil. The strains of S. pneumoniae were isolated from nasopharyngeal aspirates of children with CAP treated at Children's Hospital Albert Sabin (HIAS). For the determination of minimum inhibitory concentration (MIC) was used the E-test method for the following antibiotics: penicillin, ceftriaxone, sulfamethoxazole / trimethoprim, amoxicillin, clindamycin and erythromycin. Genotyping of strains of S. pneumoniae was performed by multiplex PCR technique. 527 samples of children with CAP were isolated S. pneumoniae in 30.17%. 126 isolates from patients found a resistance rate of 25.8% for penicillin, 81.2% to sulfamethoxazole / trimethoprim, from 21.4% to erythromycin, 19% to clindamycin and 0.8% for ceftriaxone and amoxicillin. Of the 102 genotyped strains, the most commonly found serotypes were 6A / 6B, followed by 14, 19A and 19F. They selected 29 strains resistant to penicillin for detection of protein modifications penicillin binding (PBP). Found change in PBP 1a in 69%, while for the PBP 2b and PBP 2x all tested strains showed change. As for clindamycin and erythromycin were selected 24 strains for the detection of gene ermB. Of the 24 strains tested, 79.2% had ermB gene. This study generated data on the prevalence of children with CAP S. pneumoniae revealed phenotypic and genotypic data on the resistance of the isolated front to antimicrobials used in clinical and distribution of serotypes of pneumococcus in children with CAP treated at HIAS.